Gonococcal arthritis in young woman: case report - Chambô Filho, Antônio; Rabelo, Priscila C. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
The arthritis is a complication of the gonococcical illness. It has its importance for representing highly about 50% of the infectious arthritis in youngadults e being destructive. The objective of this work is to present the clinical, diagnostic picture and treatment of a case of followed gonococcical arthritis in the service of gynecology of the Santa Casa de Misericórdia of the Vitória, Espírito Santo State. The case of a patient of 20 years is told, with active sexual life, of partner-economic classroom decrease, that was taken care of in this service with clinical picture of arthritis in the right knee and functional restric-tion. It was interned, submitted the complete clinical examination and the complementary examinations, with strong suggestive findings of gonoccocical arthritis. The therapeutical empiricist with antibiotic against the Neisseria gonorrhoeaewas initiated while the culture of the sinovial liquid andthe cervix was waited. Excellent reply in 48 hours, what it complemented the diagnosis of gonococcical arthritis, added to the positive culture of thecervix. One observed it importance of if suspecting of this diagnosis in sexually active patient young e, investigating in the primary focus, as the cervix, and to treat precociously, as praised for the Health Department, to break the chain of transmission of this STD and to prevent sequels.